The effect of maize seed coating with different fungicides and insecticides on germination traits - Mohammad Reza Mirzaei (علوم و فناوری بذر ایران, 2022)
Application of fungicides and insecticides in seed coating technology to control pathogen and pest early in the growing season to reduce damage to seedling emergence and plant establishment is essential. In this study, carboxyl tyram, lamardor, and maxim XL 035 fungicides and Cruiser FS 350, Cruiser FS 600 and Gaucho insecticides were used for coating the seed of two maize cultivars. The results showed that the coating maize seed with different fungicides and insecticides has significant effect on germination traits of the seeds. Germination rate, seedling emergence rate and seedling growth and finally dry weight were affected by the interaction of fungicide and insecticide in maize seed coating. In general, fungicidal and insecticidal formulations that have an increasing effect on seedling emergence rate and decrease average seedling emergence time, increased vegetative growth and eventually seedling weight. Maize seeds coating with Maxim XL + Cruiser 600, increased the dry weight of seedlings by 49.7% compared with uncoated seed under laboratory condition. Finally, based on germination traits in laboratory and greenhouse, Maxim XL 035 FS fungicide with Cruiser FS 600 or 350 insecticids, and Vitavax fungicide with Cruiser FS 600 insecticid, as the best combination of fungicide and insecticide are recommended for maize seed coating.